1996
DOI: 10.1148/radiology.201.3.8939220
|View full text |Cite
|
Sign up to set email alerts
|

Postprandial splanchnic hemodynamic response in patients with cirrhosis of the liver: evaluation with "triple-vessel" duplex US.

Abstract: Postprandial portal hyperemia is mainly due to mesenteric arterial vasodilation; reduced postprandial portal hyperemia in patients with cirrhosis is attributable to portocollateral runoff.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
23
0
3

Year Published

1999
1999
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(30 citation statements)
references
References 0 publications
4
23
0
3
Order By: Relevance
“…As reported previously, our study also showed that portal blood flow increases significantly 30 minutes after food intake [6]. However, there were no significant changes in parameters related to perfusion, such as D * and PF, after food intake.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…As reported previously, our study also showed that portal blood flow increases significantly 30 minutes after food intake [6]. However, there were no significant changes in parameters related to perfusion, such as D * and PF, after food intake.…”
Section: Discussionsupporting
confidence: 90%
“…Portal blood flow is usually dominant at about 75% and the remaining 25% is by arterial flow. The portal flow increases markedly with diet compared to arterial flow [6]. Currently there are only a few reports on whether the increase in portal flow affects IVIM parameters (including the concept of microcirculation) and whether T2 * value is dependent on blood flow [7].…”
Section: Introductionmentioning
confidence: 99%
“…Progressivamente, dificuldades relacionadas ao método foram sendo reconhecidas e equacionadas para que esta técnica pudesse ser utilizada eficientemente no estudo deste sistema vascular (3,7,20,22,27,28) . Sua importância no estudo da síndrome hipertensiva portal ficou estabelecida quando, apesar das dificuldades inerentes ao método, foi avaliado o prognóstico de pacientes com cirrose hepática (2,8,9,10,11,12,13,17,18,25,26,29,30) . Tais estudos, entretanto, foram realizados predominantemente em pacientes portadores de cirrose hepática, mas suas contribuições podem ser estendidas à investigação fisiopatológica do sistema portal na fibrose hepática esquistossomótica.…”
Section: Comentáriosunclassified
“…[2][3][4][5] Hepatic blood flow and vascular resistance have been shown to be positively correlated with liver stiffness. 6 As food intake is known to be associated with an increase in splanchnic and hepatic blood circulation in healthy subjects as well as in cirrhotic patients, 7,8 it has been postulated that food intake could elevate and thus overestimate LSM values. To date, three clinical studies have assessed the effect of meal ingestion on LSM values using transient elastography [9][10][11] reporting a significant increase in LSM after food intake.…”
Section: Introductionmentioning
confidence: 99%